Penerapan Metode Server In Random Order (SIRO) Pada Aplikasi Billing Ruang Karaoke Berbasis Local Area Network (LAN) - Sobirin Harahap; Pristiwanto Pristiwanto (JURIKOM (Jurnal Riset Komputer), 2019)
Karaoke is an entertainment facility that allows one to sing well accompanied by music without having to memorize the lyrics of the song. Another facility at a karaoke is being able to adjust the high and low tones of a song, adjust the tempo of the song, adjust the background sound and vocals of the singer. To manage a karaoke properly, a guest queue is arranged to enter the room and the song is played. Song playback on the karaoke room is done on the server computer or on the client computer using computer network facilities. The server computer is useful as a source of data for guest data, song data and billing data. Because the karaoke room is limited, then to arrange the queue of guests who want to enter the room is arranged by the Serve In Random Order (SIRO) queue method. By using the SIRO queue method and LAN network on karaoke management, the making and reporting of karaoke receipts can be made quickly.